Lighting a Latern in the Storm: The Transformation of Professional and Spiritual Identity of Special Guidance Teachers in Indonesia - Imron Muzakki; Novi Wahyu Winastuti (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: Inclusive education in Indonesia places Special Guidance Teachers/GPK in a central position. However, it also burdens them with severe systematic challenges, ranging form competency gaps and role ambiguity to resource limitations, which leads to a high risk of professional burnout. This study aims to analyse the transformative impact of a professional development program themed "Lighting the Latern", designed for GPKs. The analysis focuses on the shift in professional identity and the role of spirituality as a source of resilience and motivation. Methodology: This research uses a case study approach wirh a mixed-methods design. The results indicate a very high level of satisfaction with the program.Results: The qualitative analysis reveals three pillars of transformation: (1) mastery of practice through the technical skills of creating Individualized Education Programs (IEPs); (2) a metaphorical identity shift from a reactive "problem extinguisher" to a proactive "lantern" that illuminates students' potential; and (3) a profound affective and spiritual impact, marked by a rekindled spirit and a redefinition of the profession as a calling. Applications/Originality/Value: This study concludes that effective professional development for GPKs must go beyond the transfer of technical skills and consciously integrate identity formation, purpose-making, and the strengthening of professional spirituality to build sustainable resilience.